Fresh Seed Dormancy in Groundnut: Mechanisms, Factors, and Implications for Crop Improvement – a Review - RS BHAT; RV HUNJE; SS BHARATH (Seed Research, 2026)
Groundnut (Arachis hypogaea L.) is a globally important oilseed and legume food crop. However, the absence of fresh seed dormancy (FSD) in the most commonly grown Spanish bunch type varieties presents a significant hurdle to groundnut productivity and quality. Given its economic significance, research is underway to investigate the mechanisms and factors contributing to FSD in model systems, with implications for groundnut cultivation. Recent reviews have emphasized remarkable advancements in unravelling genetic control, molecular mechanisms, and the physiological and environmental factors influencing germination and dormancy across diverse plant species. In this context, we examine the latest research findings concerning FSD in groundnut, placing a stronger emphasis on the genetic factors associated with FSD. Furthermore, we explore the attempts aimed at breeding superior genotypes to enhance groundnut improvement.